2019
DOI: 10.1111/add.14794
|View full text |Cite
|
Sign up to set email alerts
|

Does child maltreatment predict alcohol use disorders in young adulthood? A cohort study of linked notifications and survey data

Abstract: Background and aims Most studies of the association between child maltreatment and subsequent problem alcohol use are retrospective. We studied the association of prospectively substantiated child maltreatment with problem alcohol use in adulthood. Design We used a prospective cohort record linkage correlational design using data from a statutory child protection agency of prospectively substantiated child maltreatment linked to a birth cohort from a major metropolitan maternity hospital. Setting The Mater‐Uni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 32 publications
2
29
0
Order By: Relevance
“…Another study using the ACE questionnaire found that CM primarily accounted for mental health symptoms in adolescents (Negriff, 2020). A prospective cohort study of young people found that participants who had experienced emotional abuse were significantly more likely to report heavy alcohol use (Kisely et al, 2019). This supports Felitti et al (1998) in their speculation that those with higher ACE scores engage in health harming behavior, such as heavy alcohol use or smoking, as a stress coping mechanism.…”
mentioning
confidence: 99%
“…Another study using the ACE questionnaire found that CM primarily accounted for mental health symptoms in adolescents (Negriff, 2020). A prospective cohort study of young people found that participants who had experienced emotional abuse were significantly more likely to report heavy alcohol use (Kisely et al, 2019). This supports Felitti et al (1998) in their speculation that those with higher ACE scores engage in health harming behavior, such as heavy alcohol use or smoking, as a stress coping mechanism.…”
mentioning
confidence: 99%
“…There are a range of simple to more sophisticated analytical methods of handling missing data that can be applied to reduce bias in reported outcomes. The simplest method reported was listwise deletion [4,21,59,97,98] and including missing data as a separate category for each covariate in regression analysis (Missing Indicator Method) [47,81,[93][94][95][96]. Sophisticated methods included multiple imputation using Markov chain iterative regression methods (MCMC) [94], multiple imputation using chained equations (MICE) [45], and multiple imputation using the fully conditional specification (FCS) method [99] (S3 Table ).…”
Section: Biases Reportedmentioning
confidence: 99%
“…Even though the attrition rate was not mentioned in almost half of the studies, attrition was described for 63% of all studies. The review identified attrition as occurring due to loss of follow-up or differential attrition occurring among families with reported cases of substantiated maltreatment, those from higher socio-economic disadvantaged backgrounds and among males and indigenous people (particularly among MUSP studies) [4,21,46,82,97,98,101,102]. Other attrition reported was death or early infant loss [47,55,93,96], non-response [47] and emigration [47,55].…”
Section: Plos Onementioning
confidence: 99%
“…If such liability is manifest initially in adolescent substance use, this use may increase the vulnerability to both later substance misuse and psychosis (Khokhar 2018), illustrating the interactive and dynamic nature of the relationship between substance use and psychosis. Similarly, stress (arising from early adversity and/ or more recent life events) is both a shared risk factor for psychosis and substance use (Mizrahi 2016;Valentino 2019;Kisely 2020) and a risk factor that may, in combination with substance use, cumulatively increase the risk of psychosis (Arranz 2018). A history of multiple acute and chronic adverse experiences over the life course (e.g.…”
Section: Shared Risk For Psychiatric Disorder and Substance Misusementioning
confidence: 99%
“…Similarly, stress (arising from early adversity and/or more recent life events) is both a shared risk factor for psychosis and substance use (Mizrahi 2016; Valentino 2019; Kisely 2020) and a risk factor that may, in combination with substance use, cumulatively increase the risk of psychosis (Arranz 2018). A history of multiple acute and chronic adverse experiences over the life course (e.g.…”
Section: Relationship Between Substance Use/misuse and Mental Illnessmentioning
confidence: 99%